2020
DOI: 10.3390/ijms21093146
|View full text |Cite
|
Sign up to set email alerts
|

Designing Single-Molecule Magnets as Drugs with Dual Anti-Inflammatory and Anti-Diabetic Effects

Abstract: We have designed and synthesized two novel cobalt coordination compounds using bumetanide (bum) and indomethacin (ind) therapeutic agents. The anti-inflammatory effects of cobalt metal complexes with ind and bum were assayed in lipopolysaccharide stimulated RAW 264.7 macrophages by inhibition of nitric oxide production. Firstly, we determined the cytotoxicity and the anti-inflammatory potential of the cobalt compounds and ind and bum ligands in RAW 264.7 cells. Indomethacin-based metal complex was able to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It was reported that the therapy of an ophthalmic in situ gel formulation incorporating disulfiram (DIS) nanoparticles (Dis-NPs/ISG) might contribute to restore retinal dysfunction in diabetic retinopathy (DR), a diabetic vascular lesion (Deguchi et al, 2020 ). Bumetanide also has been demonstrated to play an important role in antidiabetic activity with low in vitro cell toxicity through antiinflammatory effects (Navas et al, 2020 ) and can reduce diabetic vascular dysfunction by suppression of angiogenesis (Topper et al, 1997 ; Guzel et al, 2020 ). Ambroxol can significantly inhibit proinflammatory cytokines, reduce lung inflammation, and accelerate recovery by reducing vascular permeability in acute lung injury (Su et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the therapy of an ophthalmic in situ gel formulation incorporating disulfiram (DIS) nanoparticles (Dis-NPs/ISG) might contribute to restore retinal dysfunction in diabetic retinopathy (DR), a diabetic vascular lesion (Deguchi et al, 2020 ). Bumetanide also has been demonstrated to play an important role in antidiabetic activity with low in vitro cell toxicity through antiinflammatory effects (Navas et al, 2020 ) and can reduce diabetic vascular dysfunction by suppression of angiogenesis (Topper et al, 1997 ; Guzel et al, 2020 ). Ambroxol can significantly inhibit proinflammatory cytokines, reduce lung inflammation, and accelerate recovery by reducing vascular permeability in acute lung injury (Su et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO), a molecule mediator in acute or chronic inflammation, is produced by constitutive or inducible nitric oxide synthases (iNOS). Its production is activated in response to pro-inflammatory signals as cytokines such as TNFα (tumor necrosis factor α) or INF-γ (interferon-γ), enterotoxin, or LPS (either bacterial lipopolysaccharide), in macrophages [ 44 ]. Here, the decrease of NO concentration has been used as an indirect marker of the inflammatory process [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its production is activated in response to pro-inflammatory signals as cytokines such as TNFα (tumor necrosis factor α) or INF-γ (interferon-γ), enterotoxin, or LPS (either bacterial lipopolysaccharide), in macrophages [44]. Here, the decrease of NO concentration has been used as an indirect marker of the inflammatory process [44,45]. In the inflammatory response process, NO is released as an intermediate or second messenger.…”
Section: Effects Dcf N-derivatives In the Inflammatory Procesmentioning
confidence: 99%
“…Moreover, Navas et al. 38 also showed that indomethacin conferred no cytotoxicity on cell viability in vitro .…”
Section: Discussionmentioning
confidence: 99%